2019
DOI: 10.1098/rsif.2018.0960
|View full text |Cite
|
Sign up to set email alerts
|

Quenching active swarms: effects of light exposure on collective motility in swarming Serratia marcescens

Abstract: Swarming colonies of the light-responsive bacteria Serratia marcescens grown on agar exhibit robust fluctuating large-scale flows that include arrayed vortices, jets and sinuous streamers. We study the immobilization and quenching of these collective flows when the moving swarm is exposed to intense wide-spectrum light with a substantial ultraviolet component. We map the emergent response of the swarm to light in terms of two parameters—light intensity and duration of exposure—and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 44 publications
3
63
0
Order By: Relevance
“…In collectively-moving swarms, individual self-propelling cells are influenced by steric and hydrodynamic interactions with their neighbors 7,9,10,19,24 . These interactions result in complex structural and flow features including fluctuating regions of high vorticity and streamers as seen in Figure 1(a) (see also 24,25 ).The intensity and transient of these emergent flows is clearly evidenced upon seeding the swarm with small 2 µm colloidal spheres; these particles are strongly advected by the bacteria and follow tortuous trajectories as shown in Figure 1(b). The mean square displacement obtained from long time measurements provides an effective diffusivity that characterizes the activity of the suspension 24 .…”
Section: Features Of the Swarming Base State Prior To Exposurementioning
confidence: 96%
See 4 more Smart Citations
“…In collectively-moving swarms, individual self-propelling cells are influenced by steric and hydrodynamic interactions with their neighbors 7,9,10,19,24 . These interactions result in complex structural and flow features including fluctuating regions of high vorticity and streamers as seen in Figure 1(a) (see also 24,25 ).The intensity and transient of these emergent flows is clearly evidenced upon seeding the swarm with small 2 µm colloidal spheres; these particles are strongly advected by the bacteria and follow tortuous trajectories as shown in Figure 1(b). The mean square displacement obtained from long time measurements provides an effective diffusivity that characterizes the activity of the suspension 24 .…”
Section: Features Of the Swarming Base State Prior To Exposurementioning
confidence: 96%
“…Structural information such as size of coherently arrayed structures and length scales over which structural features are correlated may thus be obtained. Using these plugins we found that these domains exhibited a distribution of sizes, typically between 10-20 µm with continuously changing orientational fields due to emergent flows 25 . Figure 1(d) shows the result of such an image based analysis of the structural features demonstrating the presence of many intertwined aligned domains.…”
Section: Collective Flows In the Interphase Regionmentioning
confidence: 99%
See 3 more Smart Citations